Effectiveness and Safety of Iguratimod Monotherapy or Combined With Methotrexate in Treating Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Ouyang, Dan; Ma, Yuan Zhi; Zou, Jie; Wang, Yong Long; Chen, Zheng; Yang, Yu Ying; Zou, Bin; Li, Xin; Cao, Jian Zhong (Frontiers in Pharmacology, 2022)
Objectives: We aimed to estimate the effectiveness and safety of iguratimod (IGU) monotherapy or in combination with methotrexate (MTX) in treating rheumatoid arthritis (RA) to provide an evidence-primarily-based foundation for clinical application. Methods: We conducted a systematic review of the meta-analysis using eight databases and two clinical trial websites searching for randomized controlled trials (RCTs) from conception to 15 March 2022, based on outcomes of patients with RA treated with IGU. The evidence quality assessment of primary outcomes was evaluated by the GRADE tool, and RevMan 5.3 and StataMP 14.0 were used to perform this research. Results: A total of 4302 patients with RA from 38 RCTs was included in this research. Pooled results demonstrated as follows: 1) Compared with methotrexate (MTX) alone, IGU alone was superior in improving ACR20 and DAS28-ESR, while having no significant difference in ACR50 and ACR70 [ACR20: (RR 1.15, 95% CI 1.05–1.27, p = 0.004); ACR50: (RR 0.97, 95% CI 0.66–1.44, p = 0.88); ACR70: (RR 0.92, 95% CI 0.45–1.90, p = 0.83); DAS28-ESR: mean difference (MD) −0.15, 95% CI −0.27 to −0.03, p = 0.01]. 2) Compared with MTX alone, IGU + MTX was more effective in improving ACR20, ACR50, ACR70, and DAS28-ESR. [ACR20: (RR 1.24, 95% CI 1.14–1.35, p < 0.00001); ACR50: (RR 1.96, 95% CI 1.62–2.39, p <0.00001); ACR70: (RR 1.91, 95% CI 1.41–2.57, p < 0.0001)]; [DAS28-ESR: (MD) −1.43, 95% CI −1.73 to −1.12, p < 0.00001]. 3) Compared with MTX + leflunomide (LEF), ACR20, ACR50, ACR70, and DAS28-ESR of IGU + MTX had no significant difference [ACR20: (RR 1.06, 95% CI 0.94–1.19, p = 0.38); ACR50: (RR 1.10, 95% CI 0.66–1.84, p = 0.72); ACR70: (RR 1.20, 95% CI 0.45–3.20, p = 0.71); DAS28-ESR: (MD −0.02, 95% CI −0.13 to −0.10, p = 0.77)]. 4) Compared with MTX + hydroxychloroquine (HCQ), IGU + MTX was superior in improving DAS28-ESR (MD −2.16, 95% CI −2.53 to −1.79, p < 0.00001). 5) Compared with MTX + tripterygium glycosides (TGs), IGU + MTX was more effective in improving DAS28-ESR (MD −0.94, 95% CI −2.36 to 0.48, p = 0.19). 6) There were no significant differences in adverse events (AEs) between the groups of IGU vs. MTX (RR 0.96, 95% CI 0.71–1.31, p = 0.80), IGU + MTX vs. MTX (RR 1.10, 95% CI 0.90–1.35, p = 0.34), IGU + MTX vs. MTX + HCQ (RR 0.64, 95% CI 0.29–1.42, p = 0.27), and IGU + MTX vs. MTX + TGs (RR 0.75, 95% CI 0.28–2.02, p = 0.57). The incidence of AEs in the IGU + MTX group was lower than the MTX + LEF group (RR 0.83, 95% CI 0.71–0.98, p = 0.03). Conclusion: Compared to the MTX alone subgroup, IGU alone offers clear advantages in improving ACR20 and DAS28-ESR, despite the insufficient evidence for DAS28-ESR findings. IGU + MTX shows clear benefits in improving ACR20, ACR50, ACR70, and DAS28-ESR scores compared to standard therapies. When the intervention (IGU alone or IGU + MTX) lasted for 52 weeks, it demonstrated superior efficacy in improving ACR20 of patients without prominent adverse events. Notably, IGU or IGU + MTX has apparent advantages in improving ACR20 of first-visit RA, and IGU + MTX has obvious advantages in improving DAS28-ESR of refractory RA. Furthermore, IGU + MTX does not increase the risk of leukopenia, but it can decrease the risk of liver function tests (LFTs), regardless of the age or the stage of RA. Clinical Trial Registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42022295217